ANALISIS ISI DALAM FILM “AYAT-AYAT CINTA” KARYA HANUNG BRAMANTYO - Endah Yun Yun Annisa (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This study is aims to describe the content contained in the film “Ayat-Ayat Cinta” by director Hanung Bramantyo. A film is a document consisting of stories and pictures accompanied by words and music. So that film can be made into dimensional and complex productions. This study uses a qualitatif descriptive. Data collected through audio visual media, namely by seeing and hearing an object from images and sound. Meanwhile the data collection technique used the observation technique. The data analyzed by the writer “Ayat-Ayat Cinta” are about film data, characterization, character, story line, sound effect message content, actor’s attitude, and the content and wearing clothes. This film is an islamic religious film which can be used as an alternatife for learning about islamic education.